Oral treatment with a zinc complex of acetylsalicylic acid prevents diabetic cardiomyopathy in a rat model of type-2 diabetes: activation of the Akt pathway - Korkmaz-İçöz, Sevil; Al Said, Samer; Li, Shiliang; Brune, Maik; Hegedűs, Péter; Atmanli, Ayhan; Ruppert, Mihály; Brlecic, Paige; Lehmann, Lorenz; Lahrmann, Bernd; Grabe, Niels; Most, Patrick; et al. (Cardiovascular diabetology, 2016)
Type-2 diabetics have an increased risk of cardiomyopathy, and heart failure is a major cause of death among these patients. Growing evidence indicates that proinflammatory cytokines may induce the development of insulin resistance, and that anti-inflammatory medications may reverse this process. We investigated the effects of the oral administration of zinc and acetylsalicylic acid, in the form of bis(aspirinato)zinc(II)-complex Zn(ASA)2, on different aspects of cardiac damage in Zucker diabetic fatty (ZDF) rats, an experimental model of type-2 diabetic cardiomyopathy.
Gesehen am 12.09.2019